The Impact of Credit Distribution on Productivity and Income of Farmers in Ketapang District - Muhtadi, Ammar; Widiarta, I Putu Gede Didik (Westscience Press, 2025)
This study examines the impact of credit distribution on the productivity and income of farmers in Ketapang District using a quantitative approach. Data were collected from 150 farmers through a structured questionnaire and analyzed using SPSS version 20. The findings reveal that credit distribution significantly enhances farm productivity and income, with farm productivity serving as a partial mediator in this relationship. Farmers who accessed credit demonstrated a 30% increase in crop yield and higher monthly income compared to non-credit users. Despite these positive outcomes, challenges such as high-interest rates and limited collateral were identified as barriers to credit accessibility. The study concludes that well-designed credit programs and institutional support are essential to maximizing the benefits of credit distribution for smallholder farmers.